The Construction of Chinese Metropolitan Area from the Perspective of Politics of Scale: A Case Study of Nanjing Metropolitan Area, China - Jie Yu; Wei Zhao; Junjun Zhu (Land, 2023)
The spatial political logic of the construction of Chinese metropolitan areas (CMAs) is unique and complex, involving the interaction of power, spatial production, and the construction of political rationality between multiple scales. Taking the representative Nanjing metropolitan area as an example, we use the “material–organizational–discursive” analytical framework of politics of scale theory to analyze the construction logic of CMAs. This study finds the following: (1) In general, the CMA is a high-quality spatial construction resulting from multi-city negotiation, inter-provincial collaboration, and central–territory linkage, and has generally undergone a process of increasing the power of subjects, nested power relations, frequent scale interactions, and complex interest games; among them, planning is not only a scale tool for competing for power, but also an important representation of the results of multiple power games. (2) In terms of the construction of material space, both the delineation of boundaries and the cross-border connection of infrastructure represent rational thinking and stand as two-way choices of the two power subjects in the MA based on the maintenance and expansion of their own spatial development rights. (3) In terms of organizational space construction, CMAs mainly adopt flexible means, with bilateral and multilateral cooperation at the horizontal level, while there is a certain power inequality at the vertical level. (4) In the construction of discursive space, CMAs have experienced increasing construction significance, escalating scale subjects, and overlapping discourse narratives, and the contrast of power relations has also changed. The contribution of this paper is an expansion of the analytical framework of politics of scale based on the division of spatial dimensions, which provides a new perspective for understanding the construction of CMAs, and also helps us to picture Chinese city–regionalism.